Guidelines for restoration of Pinus nigra forests affected by fires through a structured approach. Version 2 - Kakouros, P.; Σ. Ντάφης; P. Kakouros; S. Dafis (Ελληνικό Κέντρο Βιοτόπων-Υγροτόπων (ΕΚΒΥ), 2010)
Life Πάρνωνας